Prayer camps and biomedical care in Ghana: Is collaboration in mental health care possible? - Arias, D.; Taylor, L.; Ofori-Atta, A.; Bradley, E.H. (Public Library of Science, 2016)
Background Experts have suggested that intersectoral partnerships between prayer camps and biomedical care providers may be an effective strategy to address the overwhelming shortage of mental health care workers in Africa and other low-income settings. Nevertheless, previous studies have not explored whether the prayer camp and biomedical staff beliefs and practices provide sufficient common ground to enable cooperative relationships. Therefore, we sought to examine the beliefs and practices of prayer camp staff and the perspective of biomedical care providers, with the goal of characterizing interest in-and potential for-intersectoral partnership between prayer camp staff and biomedical care providers. Methods We conducted 50 open-ended, semi-structured interviews with prophets and staff at nine Christian prayer camps in Ghana, and with staff within Ghana's three public psychiatric hospitals. We used the purposive sampling method to recruit participants and the constant comparative method for qualitative data analysis. Results Prayer camp staff expressed interest in collaboration with biomedical mental health care providers, particularly if partnerships could provide technical support introducing medications in the prayer camp and address key shortcomings in their infrastructure and hygienic conditions. Nevertheless, challenges for collaboration were apparent as prayer camp staff expressed strong beliefs in a spiritual rather than biomedical explanatory model for mental illness, frequently used fasting and chained restraints in the course of treatment, and endorsed only short-termuse of medication to treat mental illness-expressing concerns that long-term medication regimens masked underlying spiritual causes of illness. Biomedical providers were skeptical about the spiritual interpretations of mental illness held by faith healers, and were concerned by the use of chains, fasting, and the lack of adequate living facilities for patients in prayer camps; many, however, expressed interest in engaging with prayer camps to expand access to clinical care for patients residing in the camps. Conclusions The findings demonstrate that biomedical care providers are interested in engaging with prayer camps. Key areas where partnerships may best improve conditions for patients at prayer camps include collaborating on creating safe and secure physical spaces and delivering medication for mental illness to patients living in prayer camps. However, while prayer camp staff are willing to engage biomedical knowledge, deeply held beliefs and routine practices of faith and biomedical healers are difficult to reconcile Additional discussion is needed to find the common ground on which the scarce resources for mental health care in Ghana can collaborate most effectively.